Application of Finite Element Package in Tertiary Engineering Education - Debnath, Sujan; Rahman, Ekhlasur (Curtin, Sarawak, 2013)
Finite Element Method (FEM) is a numerical analysis technique for obtaining approximate solutions to a wide variety of engineering problems. FEM discretises complicated physical structure into small and manageable pieces called "finite elements” to perform analysis. FEM method virtually simulates a complicated part without real construction and performs analysis in order to test the strength and design feasibility of the component or product. As a result, design reliability and efficiency can improve without any field failure. In tertiary Engineering education, students undertake a wide range of core and applied Engineering subjects such as Applied Mechanics, Fluid Mechanics, Heat Transfer, Structural Analysis and Design, and Geotechnical Engineering. A significant component of most of these subjects is assessed by laboratory based experiments. FEM can play as a significant supplementary tool to understand and visualize the underlying conception of the lab based assignments by replicating the real life problem. FEM tool can also be utilized to verify the precision of the laboratory based experimental works. Moreover, FEM can be considered as an alternative tool in places where the Engineering educational equipment is not available or very expensive. This paper presents two case studies on the application of FEM to Engineering undergraduate students in different disciplines in tertiary Engineering education and their pedagogical aspects.